Perancangan dan Implementasi Network Monitoring Sistem Menggunakan Nagios dengan Email dan SMS Alert - Hidra Amnur -; Defni - -; Deddy Prayama -; Febrina Agustin - (Pusat Penelitian dan pengabdian kepada Masyarakat (P3M) Politeknik Negeri Padang, 2014)
Network Monitoring System is a system which has a function to observe or monitor the computer network system is running. Network monitoring system can be implemented in real time in a computer network.Development of network monitoring system using the local ip and web-based applications, where the construction of this network monitoring system using CentOS 6.4 operating system as the server.Nagios is a network monitoring application based on open source that can be used according to user needs. To maximize the use of Nagios can use email and SMS as alerts.